PARK Formula Can Replace “Guide to Medical Certificate” Published by Korean Medical Association in Deciding the Treatment Duration - Chan Yong Park; Kwang Hee Yeo; Sora Ahn (Journal of Trauma and Injury)
Purpose Many doctors have difficulty in deciding the treatment duration in trauma patients to write in the casualty medical certificate. We tried to find a solution for this problem by using abbreviated injury scale (AIS). Methods A total of 39 patients treated in our regional trauma center who requested an author to write treatment duration on casualty medical certificate from January 2014 to April 2017 were included. And the treatment duration was decided based on the PARK Formula (AIS). PARK Formula (AIS)=(AIS×2) ~ ([AIS×2]+2) Results Among 39 patients included and 36 (92.3%) had treatment duration on casualty medical certificate within the range of treatment duration calculated by PARK Formula (AIS). Compared to the PARK Formula (AIS), the mean value was 0.13 week (0.90 day) smaller. Comparing the treatment duration between Korean Medical Association (KMA) guideline and PARK Formula (AIS), only 22 patients (56.4%) showed agreement. The mean value was 1.02 week (7.18 days) smaller in KMA guideline. Conclusions For the decision of the treatment duration in trauma patients, utilizing worldwide used AIS scoring system is very efficient. Using PARK Formula (AIS), doctors can document the treatment duration in the casualty medical certificate with ease. KMA should provide more practical ‘treatment duration of each diagnosis in writing casualty medial certificate’ for the doctors. We recommend PARK Formula (AIS) as a good alternative for KMA guide.